STRATEGI KOMUNIKASI PROGRAM PROMO AIR BERSIH PDAM TIRTA LAWU KARANGANYAR DALAM RANGKA MENINGKATKAN JUMLAH PELANGGAN - DARWANTI, LINA (JURNAL KOMUNITAS, 2016)
This Research took the title " Strategy of Communication for Promo Water PDAM TIRTA LAWU Karanganyar Programme in order to Increase Number of Customers " ( Study of Case of Clean Water Promo PDAM Karanganyar Unit Matesih Programme ) . This research was conducted in the PDAM Karanganyar office . In the implementation of increasing the number of customers need strategies to plan and disseminate information with target to society . strategy of communications made to streamline thedissemination activities information by approaching directly , face to face and also media such as brochuresStrategy implementation are used to disseminate information directly to society . this research aims to determine directly the task relationships in the subscription increase the number of customer PDAM TIRTA LAWU Karanganyar . The research method used descriptive qualitative research is research which describes in detail by describing all the problems associated with what is being studied that is about strategy of communications made by the client relationships in order to improve number of customers. After conducted the research , it can be concluded that in the dissemination of information in order to attract public interest required communication strategies for more streamline activities dissemination informations, asprovide a more detailed explanation of the easy in obtaining clean water by using the services of PDAM . subscription required on the relationship delivery of information to the public should be clear and easy to understand so that people can understand and not wrong to use the services of one of the PDAM.